US COVID-19 EXAM FAILURE MAKES WORLD LEERY ABOUT AMERICAN EXCEPTIONALISM AND LEADERSHIP - Popa-Simil, Liviu (International Journal of Engineering Technologies and Management Research, 2021)
For a newbie in the USA, heath care, education, science and economy are presented as exceptional; the best of the world, but these nice words are not backed by reality, and it is hard to openly talk about these issues as they turn into an inconvenient truth, and the fact that truth is anti-American and anti-human makes it more difficult to correct the problems, as it turns difficult to openly acknowledge the issues and look for solutions. Trump and revealed a bunch of American truths, removed the of kindness and exceptionalism, and put in the limelight a lot of inconvenient realities of the actual USA, a country ideologically divided and under Lord , a nation sunk in alternate realities and facts, with a political leadership inept for progress. Looking to understand why this aberrant behavior in front of SARS-CoV-2 pandemic, we discovered that the F++ grade USA obtained at this “ecologic” exam, is routed in education of the last 50 years, that produced such population with very low real IQ, but loud arrogant and oblivious of their situation, with little respect for reality and knowledge. From the education stand point, the thinks appear even more complicated, because failures in education are routed in society, and the education system produced exactly what society asked and paid for, everything becoming a “chicken or egg” problem, under “what to solve first” dilemma The present research was looking to find an answer to this very complex problem, at minimum to openly list the issues, and propose idealistic solutions, looking to become a wake-up moment not only for the USA but for many other nations which are confronted with the same issues, of a decadent democracy and consumerist economy, without pleading for extreme left solution manifested autocratic regimes.